2012
DOI: 10.1007/s10646-012-0895-2
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of environmental stress: cellular biomarkers and reproductive responses in the Sydney rock oyster (Saccostrea glomerata)

Abstract: We measured a suite of common biomarker responses for the first time in the Sydney rock oyster Saccostrea glomerata to evaluate their utility as biological effects measures for pollution monitoring. To examine the relationship between biomarker responses and population level effects, fertilisation and embryo development assays were also conducted. Adult oysters were deployed in two contaminated estuaries and a reference estuary in Sydney, Australia. The concentrations of various contaminants (metals and polycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 59 publications
0
21
0
2
Order By: Relevance
“…Oysters (C. hongkongensis) in most sampling sites contained high concentrations of several metals such as Cd, Cu, and Zn. If we converted the metal concentrations to a wet weight basis using a wet to dry weight ratio of oysters (8)(9)(10) measured in the present study, Cd concentrations in oysters would exceed the 2 mg/kg safety limit in most of the sites [19]. Furthermore, our measurements suggested that the dominant metal pollution on the eastern side was Cu, Ni, and Zn, similar to an earlier study identifying 2 hot spots of Cu pollution in surface sediments on the eastern side of the Pearl River estuary [5].…”
Section: Trace Metals In Oystersmentioning
confidence: 99%
“…Oysters (C. hongkongensis) in most sampling sites contained high concentrations of several metals such as Cd, Cu, and Zn. If we converted the metal concentrations to a wet weight basis using a wet to dry weight ratio of oysters (8)(9)(10) measured in the present study, Cd concentrations in oysters would exceed the 2 mg/kg safety limit in most of the sites [19]. Furthermore, our measurements suggested that the dominant metal pollution on the eastern side was Cu, Ni, and Zn, similar to an earlier study identifying 2 hot spots of Cu pollution in surface sediments on the eastern side of the Pearl River estuary [5].…”
Section: Trace Metals In Oystersmentioning
confidence: 99%
“…A significant deterioration of lysosomal membranes was observed in oysters exposed to resuspended contaminated sediments, with destabilization rates as high as 60% in some treatments. Recent studies on the Sydney rock oyster and other bivalves have shown that these rates of destabilization are associated with a significant reduction in normal embryo development and suggest that these oysters are suffering from significant stress . In addition, these rates of destabilization have been observed in oysters within highly modified and more contaminated estuaries , where the combined stressors also resulted in changes in communities of larval fish bacteria , and invertebrates .…”
Section: Discussionmentioning
confidence: 99%
“…TSS ¼ total suspended solids; MDA ¼ malondialdehyde. significant stress [47][48][49]. In addition, these rates of destabilization have been observed in oysters within highly modified and more contaminated estuaries [32,50], where the combined stressors also resulted in changes in communities of larval fish [51] bacteria [52,53], and invertebrates [2].…”
Section: Cellular Responses To Resuspended Contaminated Sedimentsmentioning
confidence: 94%
“…In a related example, salinities greater than 15 ppt are associated with P.marinus infection and Dermo disease among subtidal Crassostrea virginica oysters (Ford and Tripp, 1996;Elston and Ford, 2011;Burge et al, 2014;Lafferty et al, 2015), but not among intertidal oysters that in many instances appear to be thrive in high salinity waters (O'Beirn et al, 1997;Bobo et al, 1997;Drexler et al, 2013;Volety et al, 2009Volety et al, , 2014. In some instances, abiotic factors interact to influence the production and activity of enzymes associated with cellular defenses (e.g., Akberali and Trueman, 1985;Jenny et al, 2002;Edge et al, 2012;Soudant et al, 2013). Sublethal multi-stressor impacts can be evaluated in molluscs using a suite of 'subtle' cellular biomarkers, including heat shock proteins (e.g., Akberali and Trueman, 1985;Ringwood et al, 1999Ringwood et al, , 2002Sung et al, 2011;Edge et al, 2012).…”
Section: Abiotic Determinants Of Diseasementioning
confidence: 99%
“…In some instances, abiotic factors interact to influence the production and activity of enzymes associated with cellular defenses (e.g., Akberali and Trueman, 1985;Jenny et al, 2002;Edge et al, 2012;Soudant et al, 2013). Sublethal multi-stressor impacts can be evaluated in molluscs using a suite of 'subtle' cellular biomarkers, including heat shock proteins (e.g., Akberali and Trueman, 1985;Ringwood et al, 1999Ringwood et al, , 2002Sung et al, 2011;Edge et al, 2012).…”
Section: Abiotic Determinants Of Diseasementioning
confidence: 99%